Strengthening institutional data management and promoting data sharing in the social and economic sciences - Linne, Monika; Zenk-Möltgen, Wolfgang (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2017)
In the German social and economic sciences there is a growing awareness of flexible data distribution and research data reuse, especially as increasing numbers of research funders recommend publishing research data as the basis for scientific insight. However, a data-sharing mentality has not yet been established in Germany attributable to researchers’ strong reservations about publishing their data. This attitude is exacerbated by the fact that, at present, there is no trusted national data sharing repository that covers the particular requirements of institutions regarding research data. This article discusses how this objective can be achieved with the project initiative SowiDataNet. The development of a community-driven data repository is a logically consistent and important step towards an attitude shift concerning data sharing in the social and economic sciences.